Effect of flaw inclination angle and crack arrest holes on mechanical behavior and failure mechanism of pre-cracked granite under uniaxial compression - Li Yanzhang; Zhang Chunyang; Duan Wenquan; Tan Tao (Applied Rheology)
In order to investigate the impact of flaw inclination angles (FA) and crack arrest holes on the mechanical characteristics and failure modes of combined pre-cracked granite, uniaxial compression simulation tests were conducted on specimens with different FA α and crack arrest holes using Particle Flow Code (PFC). These crack arrest holes were set at a fixed position of 5 mm from the tip of the straight crack. The simulation results showed that although crack arrest holes can change the direction of the failure mode, they had no effect on the crack initiation mode. The stress distribution under crack initiation strength was studied by analyzing the stress field through measurement circles in the PFC program. Especially, the tensile stress concentration zone determines the crack initiation mode, while the compressive stress concentration zone influences the failure mode. Based on the maximum circumferential stress criterion, the relationship between the crack initiation angle θ and the stress concentration zone was established, and a new arrangement method for crack arrest holes was proposed. This method can increase the peak strength of specimens with FA α = 0°, 45°, and 60° by 14.16, 14.12, and 14.11%, respectively, providing valuable insights for enhancing the stability of underground fractured rock masses.